2021
DOI: 10.3390/fermentation7030172
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Active Dry Yeast Could Enhance Feed Intake and Rumen Bacterial Population While Reducing Protozoa and Methanogen Population in Beef Cattle

Abstract: Urea–lime-treated rice straw fed to Thai native beef cattle was supplemented with dry yeast (DY) (Saccharomyces cerevisiae) to assess total feed intake, nutrient digestibility, rumen microorganisms, and methane (CH4) production. Sixteen Thai native beef cattle at 115 ± 10 kg live weight were divided into four groups that received DY supplementation at 0, 1, 2, and 3 g/hd/d using a randomized completely block design. All animals were fed concentrate mixture at 0.5% of body weight, with urea–lime-treated rice st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…As in previous studies ( Bayat et al., 2015 ; Phesatcha et al., 2021 ), we found an increase in DMI with ADY supplementation. In ruminants, the dietary fiber content and fiber digestibility greatly influence DMI ( de Souza et al., 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…As in previous studies ( Bayat et al., 2015 ; Phesatcha et al., 2021 ), we found an increase in DMI with ADY supplementation. In ruminants, the dietary fiber content and fiber digestibility greatly influence DMI ( de Souza et al., 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…Although the mechanism by which SC improves milk yield and components in lactating goats is not well known. The moderate positive effect of SC supplementation on milk yield in lactating goats might be related to the ability to enhance the growth of cellulolytic bacteria in the rumen, leading to an increase in total ruminal VFAs and propionate (C3) levels while decreasing acetate (C2), butyrate (C4) and the C2 to C3 ratio (46). In a similar study on cows, Zhang et al (47) found that dietary propionic acid had a positive effect on milk performance characteristics.…”
Section: Discussion E Ect Of Sc On Dmi and Milk Production Characteri...mentioning
confidence: 99%
“…Sartori et al stated that the highest total intake and average daily gain were observed in cattle supplemented with yeast [27]. e addition of dry yeast at 3g/animal/day improved total feed intake, rumen fermentation, and total bacteria populations while reducing protozoal population and methane (CH ) production in beef cattle fed with urea-urea-lime-treated rice straw [28]. ey observed that cattle fed a low plane of nutrition diet supplemented with yeast signi cantly increased average daily gain and achieved a comparable level with cattle fed with a high plane of nutrition diet, which also agrees with Geng et al [29].…”
Section: Discussionmentioning
confidence: 99%